Symptom Locus and Symptom Origin Incongruity in Runner’s Dystonia – Case Study of an Elite Female Runner - Ogasawara, Issei; Hattori, Noriaki; Revankar, Gajanan S.; Konda, Shoji; Uno, Yuki; Nakano, Tomohito; Kajiyama, Yuta; Mochizuki, Hideki; Nakata, Ken (Frontiers in Human Neuroscience, 2021)
Objectives: Runner's dystonia is a task specific dystonia that occurs in the lower limbs and trunk, with diverse symptomatology. We aimed to identify the origin of a dystonic movement abnormality using combined three-dimensional kinematic analysis and electromyographic (EMG) assessment during treadmill running. Participant: A twenty-year-old female runner who complained of right-foot collision with the left-leg during right-leg swing-phase, that mimicked right-ankle focal dystonia. Results: Kinematic and EMG assessment of her running motion was performed which showed a significant drop of the left pelvis during right-leg stance-phase, and a simultaneous increase of right hip adductor muscle activity. This resulted in a pronounced adduction of the entire right lower limb with respect to the pelvis segment. Trajectories of right-foot were seen to encroach upon left-leg area. Discussion: These findings suggested that the symptom of this runner was most likely a form of segmental dystonia originating from an impaired control of hip and pelvis, rather than a distal focal ankle dystonia. Conclusion: We conclude that, for individualized symptom assessment, deconstructing the symptom origin from its secondary compensatory movement is crucial for characterizing dystonia. Kinematic and EMG evaluation will therefore be a prerequisite to distinguish symptom origin from secondary compensatory movement.